Substrate substitution effects in the Fries rearrangement of aryl esters over zeolite catalysts. Issue 13 (10th June 2020) - Lin, Ronghe; Mitchell, Sharon; Netscher, Thomas; Medlock, Jonathan; Stemmler, René T.; Bonrath, Werner; Létinois, Ulla; Pérez-Ramírez, Javier
Abstract : The reaction scheme of the Fries rearrangement of aryl esters over zeolite catalysts strongly depends on the framework type, acidic properties, and substrate identity. Abstract : The catalytic transformation of aryl esters to hydroxyacetophenones via Fries rearrangement over solid acids is of interest to avoid the use of corrosive and toxic Lewis and Brønsted acids traditionally applied. Microporous zeolites are known to catalyze the reaction of simple substrates such as phenyl acetate, but their application to substituted derivatives has received limited attention. To refine structure–activity relationships, here we examine the impact of various parameters including the solvent polarity, water content, acidic properties, and framework type on the reaction scheme in the Fries rearrangement of p -tolyl acetate over common solid acids. The results confirm the importance of providing a high concentration of accessible Brønsted acid sites, with beta zeolites exhibiting the best performance. Extension of the substrate scope by substituting methyl groups in multiple positions identifies a framework-dependent effect on the rearrangement chemistry and highlights the potential for the transformation of dimethylphenyl acetates. Kinetic studies show that the major competitive path of cleavage of the ester C–O bond usually occurs in parallel to the Fries rearrangement. The possibility of sequentially acylating the resulting phenol depends on the substrate and reaction conditions.